Natural human Plasmodium infections in major Anopheles mosquitoes in western Thailand. Issue 1 (December 2016) - Sriwichai, Patchara; Samung, Yudthana; Sumruayphol, Suchada; Kiattibutr, Kirakorn; Kumpitak, Chalermpon; Payakkapol, Anon; Kaewkungwal, Jaranit; Yan, Guiyun; Cui, Liwang; Sattabongkot, Jetsumon
Abstract Background The Thai-Myanmar border is a remaining hotspot for malaria transmission. Malaria transmission in this region continues year-round, with a major peak season in July-August, and a minor peak in October-November. Malaria elimination requires better knowledge of the mosquito community structure, dynamics and vectorial status to support effective vector control. Methods AdultAnopheles mosquitoes were collected using CDC light traps and cow bait in 7 villages along the Thai-Myanmar border in January 2011 - March 2013. Mosquitoes were determined to species by morphological characters.Plasmodium -positivity was determined by circumsporozoite protein ELISA. Results The 2986Anopheles mosquitoes collected were assigned to 26 species, withAnopheles minimus sensu lato (s.l.) (40.32 %), An. maculatus s.l. (21.43 %), An. annularis s.l. (14.43 %), An. kochi (5.39 %), An. tessellatus (5.26 %), andAn. barbirostris s.l. (3.52 %) being the top six most abundant species.Plasmodium -infected mosquitoes were found in 22 positive samples from 2906 pooled samples of abdomens and heads/thoraxes. Four mosquito species were found infected withPlasmodium :An. minimus s.l., An. maculatus s.l., An. annularis s.l. andAn. barbirostris s.l. The infectivity rates of these mosquitoes were 0.76, 0.37, 0.72, and 1.74 %, respectively. Consistent with a change in malaria epidemiology to the predominance ofP. vivax in this area, 20 of the 22 infected mosquito samples wereP. vivax -positive. The four potential vector species all displayed apparent seasonality in relative abundance. WhileAn. minimus s.l. was collected through the entire year, its abundance peaked in the season immediately after the wet season. In comparison, An. maculatus s.l. numbers showed a major peak during the wet season. The two potential vector species, An. annularis s.l. andAn. barbirostris s.l., both showed peak abundance during the transition from wet to dry season. Moreover, An. minimus s.l. was more abundant in indoor collections, whereasAn. annularis s.l. andAn. barbirostris s.l. were more abundant in outdoor collections, suggesting their potential role in outdoor malaria transmission. Conclusions This survey confirmed the major vector status ofAn. minimus s.l. andAn. maculatus s.l. and identifiedAn. annularis s.l. andAn. barbirostris s.l. as additional vectors with potential importance in malaria transmission after the wet season.